Tathbiq Namudzaj Ta'lim Maharah al-Qiraah fi Dhaui al-Nadzariyah al-Binaiyah fi Al-Jami’ah - Hamdy, Mohammad Zainal; Ningsih, Wiwik Prasetiyo (Qismul Arab: Journal of Arabic Education, 2024)
Teachers, as those in control of the Arabic language learning process, must always pay attention to students' needs and motivation, not reduce their enthusiasm for learning Arabic, so learning models that suit students' characteristics must be presented, such as constructivism-based learning models. This research uses a qualitative approach because the data consists of verbal data, not numerical data, where data collection uses observation and interviews and is analyzed using componential data analysis. The results of this research indicate that the constructivism-based reading skills learning model consists of Exploration, Explanation, Elaboration, and Evaluation, which, in its application, influences the effectiveness of the reading skills teaching process at Darul Ulum Banyuanyar Islamic University Pamekasan and to obtain it. The participating students were more interested and put effort into the teaching and learning process, especially in the learning activities from beginning to end. In addition, the goal of education is not limited to understanding texts but rather discovering them in their experiences and knowledge.